THE IMPACT OF COMPANSATION AND MOTIVATION TO EMPLOYEES’ JOB SATISFACTION AT PT PELOPOR AVONTURIR CAMPINDO JAKARTA - Tjalla, Awaluddin; Angga, Gregorius; Mardi, Mardi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
This research is to find out how is the employees’ job satisfaction at PT Pelopor, and how the impact of compansation and motivation to job satisfaction. Research will be conducted at PT. Pelopor Avonturir Campindo. In accordance with the title, then that will be examined are all employees of PT. Pelopor Avonturir Campindo. This study does not use samples, so the entire population to be studied because the number of employees at PT. Pelopor Avonturir Campindo only numbered thirty- three (33) staff. And the result shown that (1) there is a significant effect between Job Satisfaction Employee Compensation for PT. Pelopor Avonturir Campindo, (2) There is a significant effect of Motivation on Employee Job Satisfaction PT. Pelopor Avonturir Campindo; (3) There is a significant influence jointly between Compensation and Motivation on Employee Job Satisfaction PT. Pelopor Avonturir Campindo.